2001
DOI: 10.1161/01.hyp.37.2.554
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in a Rat Model of Obesity-Induced Hypertension

Abstract: Abstract-The mechanisms underlying the development of hypertension in obesity are not yet fully understood. We recently reported the development of hypertension in a rat model of diet-induced obesity. When Sprague-Dawley rats (nϭ60) are fed a moderately high fat diet (32 kcal% fat) for 10 to 16 weeks, approximately half of them develop obesity (obesity-prone [OP] group) and mild hypertension (158Ϯ3.4 mm Hg systolic pressure), whereas the other half (obesity-resistant [OR] group) maintains a body weight equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
176
5
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(200 citation statements)
references
References 57 publications
15
176
5
4
Order By: Relevance
“…OX accompanying hypertension in animal models includes spontaneous hypertension, 22 renovascular hypertension, 23 deoxycorticosterone acetate-salt hypertension model 24 and obesity-related hypertension. 25 Moreover, reducing superoxide radicals by infusion of SOD significantly decreases BP in spontaneously hypertensive rats. 26 In humans, hypertension is also considered a state of OX that can be related to the development of artherosclerosis 27 and other hypertension-induced organ damage, 28 microalbuminuria.…”
Section: Discussionmentioning
confidence: 98%
“…OX accompanying hypertension in animal models includes spontaneous hypertension, 22 renovascular hypertension, 23 deoxycorticosterone acetate-salt hypertension model 24 and obesity-related hypertension. 25 Moreover, reducing superoxide radicals by infusion of SOD significantly decreases BP in spontaneously hypertensive rats. 26 In humans, hypertension is also considered a state of OX that can be related to the development of artherosclerosis 27 and other hypertension-induced organ damage, 28 microalbuminuria.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, reports indicate that redox signaling mediates central AngII-induced cardiovascular responses. [6][7][8][9][10] As obesity is associated with systemic oxidative stress, 13,33 we hypothesized that HF diet-induced obesity could increase superoxide production and/or reduce antioxidant capacity in the brain resulting in elevated SNS activity and blood pressure. In this study, we found that NOX2, the main membrane-associated subunit of NADPH oxidase, and two regulatory subunits, p47 phox and p67 phox , are significantly upregulated in response to HF feeding in the hypothalamus resulting in increased NADPH oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…11 On the other hand, overexpression of inducible NO synthase (iNOS) in the rostral ventrolateral medulla increases oxidative stress and elevates SNS activity. 12 As obesity affects both redox signaling and NO synthesis throughout the body, [13][14][15] there is a possibility that oxidative stress and reduced bioavailability of NO in cardiovascular regulatory nuclei mediate, at least in part, sympathoexcitation and blood pressure elevation in response to obesity.…”
Section: Introductionmentioning
confidence: 99%
“…24,26 Immunohistochemistry Formalin-fixed, paraffin-embedded sections were processed for antigen retrieval and incubated with a primary polyclonal antibody for 1:1 Cys,His,Lys-4-hydroxy-2-nonenal (HNE) adducts (Calbiochem; dilution 1:750). The slides were stained with reagents from a commercially available kit (Immuno Pure Metal Enhanced DAB substrate kit, Pierce).…”
Section: Bp Measurementsmentioning
confidence: 99%
“…27 RNA (1 g) was reverse-transcribed (RT) and amplified by polymerase chain reaction (PCR) as previously described. 26 The following pairs of forward and reverse primers were used: PPAR␥1,2, 5Ј-TCCGTG ATGGAAGACCACTC-3Ј and 5Ј-CCCTTGCATCCTTCACAAGC-3Ј; and ␤-actin, 5Ј-CGTAAAGACCTCTATGCCAA-3Ј and 5Ј-CTCCAGTGCCAAGGTC TGAA-3Ј. The neuronal (nNOS) and endothelial (eNOS) NO synthase primers were described previously.…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%